Coronary Artery Aneurysms in Kawasaki Disease: Risk Factors for Progressive Disease and Adverse Cardiac Events in the US Population. Issue 9 (15th September 2016) - Friedman, Kevin G.; Gauvreau, Kimberly; Hamaoka‐Okamoto, Akiko; Tang, Alexander; Berry, Erika; Tremoulet, Adriana H.; Mahavadi, Vidya S.; Baker, Annette; deFerranti, Sarah D.; Fulton, David R.; Burns, Jane C.; Newburger, Jane W.
Abstract : Background: The natural history of coronary artery aneurysms (CAA) after intravenous immunoglobulin (IVIG) treatment in the United States is not well described. We describe the natural history of CAA in US Kawasaki disease (KD) patients and identify factors associated with major adverse cardiac events (MACE) and CAA regression. Methods and Results: We evaluated all KD patients with CAA at 2 centers from 1979 to 2014. Factors associated with CAA regression, maximum CA z ‐score over time ( z Max), and MACE were analyzed. We performed a matched analysis of treatment effect on likelihood of CAA regression. Of 2860 KD patients, 500 (17%) had CAA, including 90 with CAA z ‐score >10. Most (91%) received IVIG within 10 days of illness, 32% received >1 IVIG, and 27% received adjunctive anti‐inflammatory medications. CAA regression occurred in 75%. Lack of CAA regression and higher CAA z Max were associated with earlier era, larger CAA z ‐score at diagnosis, and bilateral CAA in univariate and multivariable analyses. MACE occurred in 24 (5%) patients and was associated with higher CAA z ‐score at diagnosis and lack of IVIG treatment. In a subset of patients (n=132) matched by age at KD and baseline CAA z ‐score, those receiving IVIG plus adjunctive medication had a CAA regression rate of 91% compared with 68% for the 3 other groups (IVIG alone, IVIG ≥2 doses, or IVIG ≥2 doses plus adjunctive medication). Conclusions: CAA regression occurred in 75% of patients. CAA z ‐score at diagnosis was highly predictive of outcomes, which may be improved by early IVIG treatment and adjunctive therapies.